Simvastatin attenuates cisplatin-induced kidney and liver damage in rats - ERCAN, FERİHA; YÜKSEL, MERAL (ELSEVIER IRELAND LTD, 2007)
Statins have anti-inflammatory effects that are not directly related to their cholesterol-lowering activity. This study aimed to investigate the effect of simvastatin on the extent of tissue damage in cisplatin-induced nephrotoxicity and hepatotoxicity. The rats received a single intravenous injection of 2.5 mg kg(-1) cisplatin. Other groups received either simvastatin (1 mg kg(-1)) or the vehicle (ethanol: saline) intraperitoneally for 10 days beginning 5 days prior to cisplatin injection. All animals were decapitated 5 days after cisplatin administration. Trunk blood was collected and analyzed for blood urea nitrogen (BUN), creatinine, alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), albumin, and total bilirubin levels. The urine samples were used for the calculation of creatinine clearance levels. The kidney and liver samples were stored for the measurement of malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen content or were processed for histopathological examinations. Formation of reactive oxygen species in tissue samples was monitored by using chemiluminescence method. Simvastation reduced the extent of both kidney and liver damage and preserved both kidney and liver functions (p < 0.01-0.001). Increase in liver MDA level with a concomitant reduction in GSH in the cisplatin group was attenuated by simvastatin treatment (p < 0.05-0.01). Increase in tissue collagen content and chemiluminescence levels in the kidney and liver samples of the cisplatin group was also reversed by simvastatin (p < 0.001). In conclusion, simvastatin is beneficial in cisplatin-induced kidney and liver dysfunction and organ damage in rats via prevention of lipid peroxidation and tissue fibrosis, preservation of antioxidant glutathione, and suppression of neutrophil infiltration. (c) 2006 Elsevier Ireland Ltd. All rights reserved.
Keywords: cisplatin; hepatotoxicity; nephrotoxicity; rat; simvastatin; CORONARY-HEART-DISEASE; RENAL CORTICAL SLICES; INDUCED NEPHROTOXICITY; LIPID-PEROXIDATION; CHOLESTEROL LEVELS; SUPEROXIDE ANION; RANDOMIZED-TRIAL; REACTIVE OXYGEN; ARTERY DISEASE; NITRIC-OXIDE